Entreprenörens ansvar för fel i utförd entreprenad efter hävning enligt AB 04 - Särskilt om avhjälpande som påföljd - Dahlberg,Ebba (2025)
When a construction contract incorporating AB 04 is terminated, the termination only covers the remaining works, since the work already performed can-not be reversed. The client retains the performed works, and the contractor is credited for their value, taking into account any defects. But what applies if defects are later discovered in the completed works? Since such defects were not considered in the valuation, the contractor has effectively received payment for work that later proves to be defective B 04 stipulates that a warranty and liability period runs from the date of termination, but does not specify what this period entails in terms of the contractor’s liability for defects after termination. Does the contractor still have a right and obligation to remedy such defects, or does the termination mean that the contractor’s liability must be fulfilled in another way? Against this background, the thesis examines the contractor’s liability for defects identified in the already completed works after termination of the construction contract. It is initially established that AB 04 Chapter 4, Section 10, regarding the warranty and liability period, does not exclude continued application of Chapter 5, Sections 5–6 after termination, which means that the con-tractor retains liability for defects under the conditions specified in those contractual provisions. It is further assessed that works required to remedy defects that had not been identified at the time of termination are not included in the concept of “remaining works”, which is what the termination explicitly refers to. Rather, “remaining works” is understood to mean those tasks which, at the time of termination, were already identified and remained to be completed in order to finalize the project. However, it is considered a legal consequence of termination that the contractor’s right and obligation to carry out work under the contract ceases. Application of AB 04 Chapter 5, Section 17 after termination, regulating remedy as a remedy for defects, must reasonably presume that the contractor still has a right to perform obligations under the contract. Accordingly, the contractor is deemed to have neither a right nor an obligation to remedy defects within the scope of their liability under AB 04 Chapter 5, Sections 5–6. Instead, a liability to compensate arises. This is based, among other things, on the understanding that AB 04 Chapter 5, Sections 17–18 are not regarded as exclusively regulating the client’s right to remedies in the event of defects. The contractor’s liability to compensate includes the client’s costs for remedying the defect, or alternatively, the economic consequences of the defect if the cli-ent does not intend to carry out any remedial work. Furthermore, it is established that the client should be obligated to notify the contractor of the defect. The general duty to give notice under AB 04 Chapter 5, Section 15 is considered to remain applicable even after termination. If this is not deemed to be the case, a construction contract incorporating AB 04 can still be supplemented with a duty to notify under dispositive law. In cases of termination due to the client's breach of contract, or pursuant to mutually agreed grounds for termination, AB 04 Chapter 8, Section 6 is not applicable. Instead, it appears that the client may bring a claim for damages under AB 04 Chapter 5, Section 11. As a general rule, however, this provision limits the contractor’s liability for damages to 15% of the contract sum, which may be problematic. Since the provision appears to apply even after termination, there is no scope to supplement a contract incorporating AB 04 with dispositive law in order to avoid the limitation. Instead, the application of AB 04 Chapter 5, Section 11 must, if the result appears unreasonable due to extensive defects, be set aside through a final assessment of reasonableness in the individual case. An alternative for the client may be to request a correction of the amount to which the completed works were valued, given that defects subsequently identified in those works were not taken into account in the valuation. Such a reassessment of the value of the completed works is considered possible, as a valuation report and the amount stated therein do not appear to be materially binding between the parties. Furthermore, a reassessment and possible correction of the valuation is not regarded as a claim for damages, but rather as an alternative legal remedy. By instead reassessing the value of the completed works, the client may thus avoid the 15% limitation in those termination situations where a claim for damages for defects would otherwise be brought under AB 04 Chapter 5, Section 11. But what applies if defects are later discovered in the completed works? Since such defects were not considered in the valuation, the contractor has effectively received payment for work that later proves to be defective. AB 04 pro-vides that a warranty and liability period begins from the date of termination but does not expressly state how liability for defects should be fulfilled after termination. Does the contractor retain the right and obligation to remedy the defect, or does termination imply that liability must be fulfilled in another way? Against this background, the thesis examines the contractor's liability for defects discovered in already completed works after termination. It is initially noted that AB 04 Chapter 4 Section 10 does not preclude continued application of Chapter 5 Sections 5–6, meaning the contractor remains liable for defects according to the conditions specified in those provisions. It is then assessed that the obligation to remedy defects not yet identified at the time of termination does not fall under the "remaining works," which termination explicitly addresses. The remaining works are instead understood as the tasks remaining to complete the contract at the time of termination. However, termination has legal consequences that mean the contractor's right and obligation to perform work under the contract ceases. Consequently, the contractor no longer has the right or obligation to remedy defects under Chapter 5 Sections 5–6. The application of Chapter 5 Section 17 reasonably re-quires that the contractor retains a right to perform in natura under the con-tract, making that provision inapplicable after termination. Instead, a liability for compensation is triggered. This follows, among other things, from the fact that Chapter 5 Sections 17–18 are not considered to exclusively regulate the client's right to remedies for defects. The contractor's liability should include the client's costs for remedying the defect, or the financial consequences of the defect if the client does not intend to correct it. This liability should, however, presuppose that the client notifies the contractor of the defect. The general notification obligation in Chapter 5 Section 15 is likely still applicable. If not, a duty to notify may be inferred from supplementary dispositive law. In cases of termination due to the contractor’s breach, the client may base a claim for damages on Chapter 8 Section 6. The contractual time limit in this provision may then apply independently of the special limitation period in the third paragraph. In other cases of termination, Chapter 5 Section 11 appears applicable. How-ever, this provision limits damages to 15% of the contract sum, which is problematic. Since the provision seems applicable, there is no room to supplement the contract with dispositive law. In individual cases where this cap leads to an unreasonable result due to the severity of the defect, the limitation may be set aside based on a final reasonableness assessment. As an alternative, the client may seek a revision of the valuation statement and the amount assigned to the completed works, since defects discovered later were not accounted for in this valuation. This requires that the valuation statement is not equated with a binding expert determination. By instead ad-justing the valuation amount, the client avoids the monetary cap in Chapter 5 Section 11. Such a revision is not considered a damages claim, but rather an alternative remedy that does not exclude the application of either Chapter 5 Section 11 or Chapter 8 Section 6.
Keywords: entreprenadrätt; AB 04; hävning; felavhjälpande; förmögenhetsrätt